Design, Analysis and Performance Study of PV-Wind-Diesel Generator Hybrid Power System for a Hilly Region Khagrachari of Bangladesh - Prodhan, M. M. H.; Talukder, A. B. M. H.; Huq, M. F.; Aditya, S. K. (Journal of Scientific Research, 2017)
In this research paper, a hybrid power generation system considering Photovoltaic (PV), Wind Turbine and Diesel generator, has been proposed for a hilly region application. The method of this study was the assortment of the elementary data of wind speed, solar radiation and additional requisite input data. The electric renewable energy software hybrid optimization model of renewable energy (HOMER) has been used for design, analysis and performance study of the system. The model has been designed to deliver an optimum pattern based on hour-by-hour data for energy convenience and loads. A number of various performance studiy like sustainability, sensitivity, cost, feasibility is performed in this research. 24 h primary AC loads, yearly wind speed and PV radiation were analyzed. Analysis divulges that this proposed hybrid power generation system would be feasible alternatives for stand alone application at rural and detached hilly localities.